Electric drive - Kutovyi, Yu. M.; Kunchenko, T. Yu.; Obruch, I. V. (Національний технічний університет "Харківський політехнічний інститут", 2024)
The book is a study guide, which contains basic information on the electric drive. The material of the manual can be useful not only students of the specified field, but also to engineering and technical personnel working in the field of automated electric drive.
Keywords: study guide; electric drive; electric drive clasification; mechanics of the electric drive; electric drive transients; DCM CE characteristic